The perception of security in the international comparative perspective - J Díez-Nicolás (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2016)
The author considers security a key value in present societies all around the world due to the general change in values since the end of the 20th century, which is characterized by a certain return to more materialistic values and a reduction of personal and economic security under the globalization. The article provides two different but complementary theoretical frameworks for the sociological study of security. The first theoretical frame was developed in the late 1970’s as a reaction to the excessive optimism generated by the high levels and rates of economic development during the previous years. Within this conceptual frame the author groups 59 countries into seven geo-cultural world regions, and identifies the change in values not only as a reduction of post-materialist values, but also as an increase in desires for greater authority in the future, particularly in more developed societies. In the second theoretical scheme all forms of social organization (political, economic, family, educational, etc.) including value systems, are instruments of adaptation of human societies to their environment. Thus, the main hypothesis here is that values change because of the levels of security in society, both personal and economic security: as security levels rise or decline, values change. The author considers both theoretically and empirically four indexes of security - personal, community, national and total. According to the European surveys data, developed countries seem to feel subjectively more secure than less developed countries, but variation even among countries within the same world geo-cultural region is very wide. On the basis of three sets of variables used to explain the four indexes of security (socio-demographic, attitudinal, national defence and a combination of the previous three) the author shows that the combined set seems to be the most robust to explain all four indexes of security. However, there is a great variation in the levels of the four types of security among the seven geo-cultural world regions, and among the countries within each region. This implies that the country continues to be the most important unit of analysis in international comparisons, which should take into account both subjective and objective measures of security.